"Is anyone walking in our neighborhoods?": Citizens' experience of the neighbourhood environment. (13th November 2019) - Middleton, N; Kleopa, D; Panayiotou, A; Kouta, C
Abstract: Background: Several generic or feature-specific neighbourhood audit tools have been developed in recent years. In the context of developing the Cyprus Neighbourhood Observation Tool for auditing urban environments (CyNOTes), a virtual ethnographic study of citizens' perceptions of their neighbourhood environment was performed. Methods: The municipality and mayor's Facebook were reviewed for posts related to neighbourhood environment over a 12-month period (e.g. regeneration projects). Comments were content analysed using a deductive as well as an inductive approach to gain an in-depth understanding of citizens' perceptions of neighbourhood environment. Results: 348 comments to 27 relevant posts were identified. The unit of analysis was sentences or short phrases and 289 CMU were identified. The central theme was "Citizens' voice". Six themes and several sub-themes emerged. "Comparisons" to contrast the differing conditions between high-profile locations versus "left out" residential neighbourhoods ("Yes, the city centre, the waterfront is a jewel, what about the neighborhoods?") or to compare their experience to "another place-another time". They express "Mixed feelings" ranging from "hope" to "disbelief" about proposed actions. Citizens are referring to "Consequences" of neighbourhood adverse environment on "Quality of Life" or "Local ecomomy and housing" and identify "Causes" in "Money and Power" or "Lack of vision and planning". They are placing "Responsibility" in both "Authorities' inaction" as well as "Everyone's role". "Suggestions" included measures related to "Law and Order" as well as "Citizens' participation". Conclusions: Citizens voice their experiences of the neighbourhood environment lack of influence and control and demand for more involvement in decision-making. They blame authorities for neighbourhood problems but also recognize the lack of individual responsibility, suggesting policing and punitive measures and stronger collective action. Key messages: A virtual ethnographic study of citizens' comments on social media offers an in-depth understanding of the neighbourhood experience. Citizens want to have a "voice" to express their concerns about neighbourhood problems as well as to participate in decision-making.